The Effectiveness Of Black Cumin Nanoemulsion Gel Concentration 10% And 15% On Staphylococcus Aureus Biofilm Thickness (In Vitro) - Praptiningsih, Rahmawati Sri; Feranisa, Anggun; Amalina, Rizki; Nur Istighfah, Jafifah Mega (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Periodontal disease is a disease that often occurs in the oral cavity with prevalence in Semarang City increasing in 2016 by 67.18% to 89.53%. One of the causes of periodontal disease is the buildup of Stapylococcus aureus bacterial biofilm during the initial colonization of the tooth pellicle formation. One herbal ingredient that can be used as an antibacterial is black cumin (Nigella sativa). Gel nanoemulsion technology has the advantage of increasing material stability. This research aims to determine the effectiveness of black cumin gel nanoemulsion on the growth of Stapylococcus aureus biofilm thickness. Methods:The treatment group consisted of black cumin gel nanoemulsion with a concentration of 10% and a concentration of 15% and the control group, namely 0.2% chlorhexidine and distilled water. Stapylococcus aureus biofilm thickness was measured using an ELISA-reader. Statistical tests were carried out using the One Way Anova test. Results: The average thickness of Stapylococcus aureus with the addition of black cumin gel nanoemulsion with a concentration of 15% was the lowest, namely 0.046, while the thickness of Stapylococcus aureus with the addition of distilled water was the highest, namely 0.158. The One Way Anova test obtained a significance figure of 0.000 (p<0.05) so it could be concluded that there were significant differences in the 4 Stapylococcus aureus thickness test groups.Conclusion: Black cumin gel nanoemulsion concentrations of 10% and 15% have antibacterial properties which can reduce the thickness of Stapylococcus aureus biofilm.